"Glory in a Host of Entomological Spoils": Beetle-Wing Embroidery and the Exhibition of India in Anglo-American Dress, 1780–1903. (2nd January 2021) - Libes, Kenna
Abstract : Iridescent, color-shifting beetle wing casings have been embroidered onto dress around the world for centuries. This paper explores a variation of the practice from its roots in Mughal-era India through its translocation and transformation by English dressmakers during the East India Company and colonial eras. This paper considers the first recorded English women to wear such garments, how and where they were made, and the intersections of fashion, exhibition, and naturalism. By examining extant textiles made for use in both countries, this paper asserts that the English-speaking world, influenced by its colonial sensibilities, appropriated and implemented a new style of beetle-wing embroidery.